A simple route for the synthesis of Fe/C composite derived from the metal-organic framework MIL-53 (Fe) - Nguyen, Duyen Thi Cam; Le, Hanh Thi Ngoc; Tran, Thuan Van; Nguyen, Oanh Thi Kim; Nguyen, Trinh Duy; Sy, Do Trung; Vo, Dai-Viet N.; Lam, Tri Duc; Bach, Long Giang; Thuan, Doan Van (Elsevier Ltd, 2019)
The Fe/C composite plays the crucial role in various practical applications, therefore, the synthesis of this composite has attracted much attention. Herein, we described the simple method for the synthesis of Fe/C composite derived from the metal-organic framework MIL-53 (Fe). The MIL-53 (Fe) precursor was initially fabricated using the solvothermal strategy, and transformed into porous Fe/C via a direct pyrolysis procedure. Both MIL-53 (Fe)and Fe/C were also characterized using the several techniques to compare the change of crystalline profile, surface chemistry, morphological property, saturation magnetization, pH point of zero charge and surface area among them. The surface areas measured revealed an enormous change from 7.6 m2 /g in MIL-53 (Fe) to 196.1 m2 /g in Fe/C the Raman spectra also gave evidence of the presence of graphitic carbon in the Fe/C structure.